Compensation circuit design for tuned half-wavelength transmission lines based on Bessel filter. (January 2022) - Cao, Pulin; Fan, Haoran; Wang, Deng; Shu, Hongchun; Yang, Bo; Han, Yiming; Dong, Jun
Highlights: It concludes that the compensation circuit for HWTL is a low-pass passive filter. The suitable type and the proper order for half-wavelength transmission lines is analyzed. The voltage distribution is simulated to verify the feasibility of the proposed method. Transient responses of tuned lines are compared to verify the superiority. Abstract: Compensation circuit, which can increase electrical length, is the most feasible solution for flexible applications of half-wavelength transmission lines (HWTL). In previous studies, it is always assumed that the compensation circuit is structured by passive components with identical parameters to represent the distribution parameter of transmission lines. However, the structure of the traditional compensation circuit is actually equivalent to that of the constant k filter, which concludes that the compensation circuit is fundamentally a low-pass filter. In consideration of basic requirements for tuned HWTL, the Bessel filter, which has smooth group delays without waveform distortion, is selected for the calculation of compensation circuit parameters in this paper. Lastly, the Bessel-based compensation circuit is compared to natural HWTL and tuned HWTL with Butterworth filter-based and traditional compensation circuits. Comprehensive cases simulated by PSCAD are undertaken, which validate that the voltage distribution of Bessel-based compensation circuits is quite similar to that of traditional compensation circuits. Moreover, electromagnetic transients can induce significant high-frequency oscillations in tuned HWTL with traditional compensation circuits, but high-frequency oscillation is significantly reduced by Bessel-based compensation circuits. Therefore, the Bessel-based compensation circuit is verified to be a better solution for tuned HWTL.